Ejection of Dust From the Ocean as a Potential Source of Marine Ice Nucleating Particles. Issue 24 (22nd December 2020) - Cornwell, Gavin C.; Sultana, Camille M.; Prank, Marje; Cochran, Richard E.; Hill, Thomas C. J.; Schill, Gregory P.; DeMott, Paul J.; Mahowald, Natalie; Prather, Kimberly A.
Abstract: Oceans are, generally, relatively weak sources of ice nucleating particles (INPs). Thus, dust transported from terrestrial regions can dominate atmospheric INP concentrations even in remote marine regions. Studies of ocean‐emitted INPs have focused upon sea spray aerosols containing biogenic species. Even though large concentrations of dust are transported over marine regions, resuspended dust has never been explicitly considered as another possible source of ocean‐emitted INPs. Current models assume that deposited dust is not re‐emitted from surface waters. Our laboratory studies of aerosol particles produced from coastal seawater and synthetic seawater doped with dust show that dust can indeed be ejected from water during bubble bursting. INP concentration measurements show these ejected dust particles retain ice nucleating activity. Doping synthetic seawater to simulate a strong dust deposition event produced INPs active at temperatures colder than −13°C and INP concentrations 1 to 2 orders of magnitude greater than either lab sea spray or marine boundary layer measurements. The relevance of these laboratory findings is highlighted by single‐particle composition measurements along the Californian coast where at least 9% of dust particles were mixed with sea salt. Additionally, global modeling studies show that resuspension of dust from the ocean could exert the most impact over the Southern Ocean, where ocean‐emitted INPs are thought to dominate atmospheric INP populations. More work characterizing the factors governing the resuspension of dust particles is required to understand the potential impact upon clouds. Plain Language Summary: Clouds are formed through the deposition of water onto aerosol particles. A rare subset of these aerosol particles, ice nucleating particles (INPs), is required for cloud droplets to freeze at temperatures warmer than −38°C and can profoundly affect climate. Unfortunately, the identity and sources of INPs in marine regions are not well understood. Dust particles from land masses can be transported over marine regions where they commonly deposit to the ocean's surface in what has been assumed to be a one‐way atmospheric loss process. We show through a combination of lab, field, and modeling studies that dust can be re‐ejected in sea spray aerosols and still act as INPs. Modeling studies indicate that oceanic dust INPs will have the greatest influence over the Southern Ocean. Key Points: Terrestrial dust deposited in seawater can be re‐aerosolized inside sea spray aerosol Re‐aerosolized oceanic dust particles retain ice nucleation activity and may add to atmospheric ice nucleating particle populations Global simulations estimate that the greatest impact of this process would be in the Southern Ocean